Exhaust and non-exhaust emissions from conventional and electric vehicles: A comparison of monetary impact values. (10th January 2022) - Liu, Ye; Chen, Haibo; Li, Ying; Gao, Jianbing; Dave, Kaushali; Chen, Junyan; Li, Tiezhu; Tu, Ran
Abstract: The switch to electric vehicles (EVs) has been incentivised by governments all over the world to reduce the use of fossil fuels and improve air quality. However, whether such a move could effectively lower the levels of pollutants as much as expected is still controversial. This study estimates the impact values of exhaust and non-exhaust emissions emitted from internal combustion engine vehicles (ICEVs) and their equivalent EVs from an economic-environmental perspective, expressed as monetary impact values, so as to ascertain the environmental effect of the switch to equivalent EVs from ICEVs. These monetary impact values were calculated according to the emission factors and damage costs of these pollutants. The results indicate that the particulate matter (PM) monetary impact values of equivalent EVs may exceed those of ICEVs, which depends primarily on the extent of regenerative braking and road type. The monetary impact values of total pollutants decrease for the move from diesel passenger cars to their equivalent EVs with 0% regenerative braking. For the conversion of petrol passenger cars to their equivalent EVs with 0% regenerative braking, however, the total monetary impact values increase on both urban and rural roads. These results can be useful for the economic-environmental assessment of vehicle exhaust and non-exhaust emissions.